Perencanaan Pembebanan Kerja Untuk Memenuhi Kebutuhan Konsumen Dengan Metode VAM - Ilyas Mas'udin (Jurnal Teknik Industri, 2000)
In trade competition for this time, then each factories must be try to completing consumer demand on precise time and quantity. One thing which influence is fluent of production. In order that production able to work smoothly, so it is necessary to conducting work resposibility to perform work operations in production process. There is exact work responsibility could be optimalizing collar worker productivity. Then, this thing have side effect to production cost. One way to create this situation is with using VAM (Vogel' Approximation menthod). On VAM, this case will be finished equivalen with transportation problem that production capacity and demand said on same squad, same total capacity and same demand. If some time this situation is not completed, then the system must be balanced out first with make capacity or demand Dummy.